Handbook of vinyl polymers radical polymerization, process, and technology - Mishra, Munmaya K.; Yagci, Yusuf 1952-; Mishra, Munmaya K. (CRC Press/Taylor & Francis, 2009)
Written by renowned researchers in the field, this handbook is primarily concerned with the physical and organic chemistry of radical vinyl polymerization. The authors survey the most recent advances, processing methods, technologies, and applications of free radical vinyl polymerization. The book features thorough coverage of polymer functionalization, photo initiation, block and graft copolymers, and polymer composites.